Larvicide Activity of Teak Wood Powder and Its Extract to Dengue Fever Mosquito - Deded S Nawawi; Anne Carolina; Cahyo Werdiningsih (Masyarakat Peneliti Kayu Indonesia, 2014)
Dengue fever is transmitted to human by Aedes aegypti mosquito. Tectoquinone of teakwood extractives could be developed as natural larvicide for the mosquito due to its antifungal and insecticidal activities. However, larvicidal activities of Indonesian teak wood extract have not been investigated to a greater exten. In the present works, the larvicidal activity of teak wood extract and wood powder against fourth-instar larvae of A. aegypti was examined for different concentration of 2-methylanthraquinone based. Heartwood sample of 45 year old tree from East Java was used for the experiment. Isolation of extractives was carried out with ethanol: toluene (1:1 v/v). The concentration of 2-methylanthraquinone of the extract was determined by Pyr-Gas Chromatography Mass Spectrometry (Pyr-GC-MS). Larvacidal activity was expressed as a mortality of larva and lethal concentration (LC50 and LC90). The 2-methylanthraquinone was conformed as the main compound of teak wood extract. Teak wood extract was an effective larvicide against A. aegypti larvae. The LC50 and LC90 of the extract were found at 7.99 and 11.87 μg ml-1 of 2-methylanthraquinone, respectively. Higher lethal concentration was required by wood powder, i.e. with LC50 and LC90 of 849.30 μg ml-1 and 1051.10 μg ml-1, respectively.Keywords: Aedes aegypti, extractives, larvicide, Tectona grandis, tectoquinone